Mind habits of outstanding school students in Salah al-Din - Waad Abid AL-Nasery, Dr.Ghaidaa (Journal of College of Education, 2022)
After the concept of habits of mind is a modern and prophetic conceptbecause it came as an evolution of the concept of intelligence and what mind habits mean. It is a pattern of the intelligent intellectual mechanisms that lead us to the factory. Choices and details about which patterns should be used at a particular time or in a particular situation without others. "Therefore, habits of mind are a cognitive structure that can be developed and taught to students The aim of the current research is to identify the mind habits of distinguished students in middle schools, the males. according to the gender variable of habits of mind The researcher adopted the Hussain Scale 2012 after reviewing a number of tools, and it was the best for the sample. It was applied by the appropriate alternatives to the distinguished school students in Tikrit, the Governor of Salah al-Din. The sample was (0) males) and (5) females from the fifth grade. The application was carried out after finding the variables. Al-Sukwiya Sis a village on the authority of the tool by extracting honesty and the ratios were 9 and verifying the stability and it was (). Distinguished schools in Tikrit, the governor of Salah al-Din, and the sample was(0) males) and (v) females) from the fifth grade and it was applied after finding the scometric variables on the instrument by extracting the apparent validity and the percentages were 89% and checking the stability and it was (). With regard to the research sample, the sample members have a good level of habits of mind, because they are in different environments of a director of teachers (advisory, new, preparing cadres), in addition to the high level of intelligence that enables them to pass a test of the Ministry of Education before they are accepted from schools The researcher (L) also found that there are no statistically significant differences between the aforementioned and female trainees, and the number of that because they have similar degrees of intelligence, i.e. mental habits at the same level, and they were subjected to the same test for acceptance and qualifications of the school staff, and a specific curricula were handed down. The researcher presented a set of recommendations and suggestions, including the preparation of A slanted drama on eminent samples and a comparative study between the level of habits of mind among distinguished students and ordinary students.